23-Prenatal stress, mood, and gray matter volume in young adulthood. Issue 4 (April 2018) - Marečková, K.; Klasnja, A.; Bencurova, P.; Andrýsková, L.; Brázdil, M.; Paus, T.
Abstract : This study aimed to determine whether prenatal stress, measured by the number of stressful life events during the first 20 weeks of pregnancy, might relate to mood dysregulation and altered brain structure in young adulthood. Participants included 93 mother – offspring pairs from a community-based birth cohort from the Czech Republic (European Longitudinal Study of Pregnancy and Childhood; ELSPAC-CZ). MRI analyses focused on overall cortical gray matter (GM) volume and GM volume of cortical regions previously associated with major depression. Higher prenatal stress predicted more mood dysregulation, particularly higher anxiety, fatigue and anger, lower overall cortical GM volume (corrected for brain size) and lower GM volume in mid-dorsolateral frontal cortex, anterior cingulate cortex and precuneus in young adulthood. We observed no Prenatal Stress by Sex interactions for any of the above relationships. We conclude that prenatal stress is an important risk factor that relates to worse mood states and altered brain structure in young adulthood irrespective of sex. Our results point to the importance and long lasting effects of prenatal programming and suggest that offspring of mothers who went through substantial stress during pregnancy might benefit from early intervention that would reduce the odds of mental illness in later life.